Gender Dimensions of the Extractive Industries : Mining for Equity - Eftimi, Adriana; Heller, Katherine; Strongman, John (World Bank, Washington, DC, 2014)
Extractive industries (EI) impacts can be positive and negative, spanning economic, social, and environmental issues. Oil, gas, and mining projects may create jobs, but may also consume farming land for their use, changing livelihoods and limiting access to water, food, and firewood. Water sources may become polluted, but new roads may be built and communities may become electrified. Markets may boom, but prices may rise steeply. Given male and female relationships to each other, to the economy, to the land, and to their communities, men and women have very different experiences of these EI impacts, and evidence increasingly demonstrates that in general women are more vulnerable to the risks, with little access to the benefits. This publication presents how and why men and women are differently impacted by EI, exploring what the implications are for business and development, and providing policy and action suggestions for how to mitigate negative impacts and amplify positive ones and how to monitor and improve results. The publication focuses primarily on larger scale commercial operations but also considers some of the issues relating to artisan and small-scale mining (ASM). The report is addressed to the stakeholders in extractive industries, i.e., oil, gas, and mining development and operations community members and leaders; government officials; and managers and staff of EI companies.